Professional autonomy: Challenges and Opportunities in Poland,Russia and Sweden - Nygren, Gunnar; Dobek-Ostrowska, Boguslawa; Anikina, Maria (Nordicom review, 2015)
Degree of autonomy is one of the key dimensions of professionalization in journalism. However, the strive for autonomy looks different in different media systems, where pressure on autonomy can come from both political and commercial powers, outside and within the media. Media development also changes the conditions for professional autonomy for journalists, in both a positive and a negative sense. In the comparative research project “Journalism in change”, the journalistic cultures in Russia, Poland and Sweden are studied. In a survey involving 1500 journalists from the three countries, journalists report on their perceived autonomy in their daily work and in relation to different actors inside and outside the media. The survey covers how the work has been changed by media developments, and how these changes have affected journalists′perceived autonomy. The results show similarities in the strive for autonomy, but also clear differences in how autonomy is perceived by journalists in the three countries.